Los observadores de clase y su posición en el campo de la enseñanza del inglés - Martínez Luengas, Miguel (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
The class observations are constant practices that are carried out in the ELT (English Language Teaching) field. When a person started studying to be an English Teacher, this person observes the school contexts, the teachers at schools/universities and is also observed by the Main Teacher and/or coordinators. In the same way, the observation is using to evaluate pedagogical/academic processes, it is done to provide feedback, to recollect data in research procedures, among other ones. However, there are some questions which are important to state about this topic, for example, who is observing classes? what is it observed for? are there different positions of the observer?  This article pretends to inquire about the unknown aspects behind the English classes’ observations and mainly, exploring the positions of the observers (subjects who are landed on this practice). These positions are in constant movement and hold voices, emotions, struggles, desires, and more characteristics inside the class observers in the ELT field. The purpose of this text deals with emerging the diverse observer subject position (s) in the ELT field.